DETERRENCE, SECURITY DILEMMA AND THE PROLIFERATION OF NUCLEAR WEAPONS IN THE INTERNATIONAL SYSTEM: A STUDY OF NORTH KOREA AND PAKISTAN - EYINA, Nkatomba Nkatomba, PhD; ANYALEBECHI, Shammah Mahakwe, PhD (European Journal of Humanities and Educational Advancements, 2024)
The proliferation of nuclear weapons remains a critical issue in international relations, particularly concerning states like North Korea and Pakistan. Both nations have pursued nuclear capabilities to address their unique security challenges, rooted in historical conflicts and regional dynamics. North Korea’s nuclear ambitions are driven by perceived threats from the United States and South Korea, while Pakistan’s nuclear strategy is shaped by its contentious relationship with India. The actions of these states have significant implications for regional and global security, leading to heightened tensions and an arms race in South Asia and East Asia. Understanding the motivations behind their nuclear proliferation and the resulting security dilemmas is essential for developing effective non-proliferation strategies and ensuring stability in these volatile regions. The study employs deterrence theory as its theoretical framework. Utilizing a qualitative research design, the method of analysis is content analysis, focusing on historical, political, and strategic contexts. The findings reveal that both North Korea and Pakistan have developed nuclear arsenals primarily as deterrents against perceived existential threats from their regional adversaries. This nuclear armament, while intended to ensure national security, exacerbates regional security dilemmas and fuels arms races. The study concludes that understanding these dynamics is crucial for crafting policies aimed at mitigating nuclear risks. Based on the above, the paper recommended among other things that there is need to strengthen diplomatic engagement and confidence-building measures to reduce tensions and prevent escalation in nuclear-armed regions